CARACTERISATION PHYSICO-CHIMIQUE ET ESTIMATION DE LA STABILITE STRUCTURALE DES SOLS AGRICOLES DE LA REGION SIDI RAHAL, SAHEL (CHAOUIA COTIERE, MAROC) - Fadwa Rafik; Najib Saber; Fatna Zaakour; Hajar Mohcine; Kaoutar Moustarhfer; Chakib Marrakchi (European Scientific Journal, ESJ, 2015)
The aim of this study is to characterize and evaluate the physical and chemical quality of agricultural soils irrigated with water from wells in the region of Sidi Rahal, Sahel (coastal Chaouia, Morocco). Thus, thirty soil samples (0 to 20cm of depth) was randomly taked from three agricultural stations and were treated for various physicochemical analyzes (texture, pH, organic matter, calcareous rate, structural stability). The results show siltysand soils with homogeneous texture, moderately basic pH (7.89 to 8.20), and 15.85% as carbonate rate. The organic material ranges from 0.3 to 2.5, the structural stability dry up and under water showed that those soils are usually unstable with a mean weight diameter (MWD) which ranges from 0.21 to 1.31 and stability index (SI) varying from 10.49 to 67.85.